Proline Exogenously Supplied or Endogenously Overproduced Induces Different Nutritional, Metabolic, and Antioxidative Responses in Transgenic Tobacco Exposed to Cadmium - Borgo, Lucélia; Rabêlo, Flávio Henrique Silveira; Budzinski, Ilara Gabriela Frasson [UNESP]; Cataldi, Thaís Regiani; Ramires, Thiago Gentil; Schaker, Patricia Dayane Carvalho; Ribas, Alessandra Ferreira; Labate, Carlos Alberto; Lavres, José; Cuypers, Ann; Azevedo, Ricardo Antunes (Springer Nature, 2021)
Proline plays adaptive roles in plant tolerance to cadmium (Cd)-induced stress, but many gaps remain to be elucidated as the responses triggered by exogenously supplied proline or endogenously overproduction are not well known. Thus, we assayed the nutritional status, metabolite profiling, and antioxidative responses in wild type and transgenic tobacco (Nicotiana tabacum L.) containing the P5CSF129A gene under control of the cauliflower mosaic virus (CaMV35S) or stress inducible rd29A promoters. The plants were exposed or unexposed to Cd (0 and 50 μmol L−1 CdCl2·H2O) for 24 and 72 h. The wild type plants were also treated with or without exogenous proline (1 mmol L−1). Plants supplied with exogenous proline exhibited lower Cd translocation from roots to leaves than plants overproducing proline, avoiding oxidative damages in the leaves of these plants. Meanwhile, tobacco overproducing proline was less susceptible to Cd-induced nutritional changes than wild type plants and presented better metabolic adjustment under Cd exposure compared to plants supplied with exogenous proline. Plants overproducing proline increased the synthesis of sugars and organic acids under Cd exposure, which contributed to absence of oxidative stress, since both superoxide dismutase and catalase were not active against Cd-induced oxidative stress in these genotypes. Plants overproducing proline under the control of rd29A presented higher proline concentration in comparison to the CaMV35S promoter. With exception of rd29A plants that presented high proline and reduced glutathione (GSH) concentrations, the other plants presented an inverse correlation between proline and GSH synthesis after 72 h of Cd exposure.
Keywords: Glutathione; Metabolite profiling; Nicotiana tabacum L; Nutrient homeostasis; Oxidative stress; P5CSF129A